Stratification algorithm for repetitive TMS in stroke (START): Results from an exploratory crossover study - Lin, Yin-Liang; Potter-Baker, Kelsey A.; Sankarasubramanian, Vishwanath; Cunningham, David A.; Li, Manshi; O'Laughlin, Kyle; Conforto, Adriana B.; Wang, Xiaofeng; Sakaie, Ken; Knutson, Jayme; Machado, Andre G.; Plow, Ela B. (Journal of the neurological sciences, 2025)
The role of contralesional motor cortices in paretic upper extremity (UE) motor recovery following stroke varies based on available structural reserve. However, an optimal measure of the reserve to stratify patients for different contralesional brain stimulation remains unknown. This study aimed to establish severity criteria distinguishing which patients benefit more from inhibitory contralesional motor cortex (M1) stimulation versus facilitatory contralesional dorsal premotor cortex (cPMd) stimulation. Twenty-four chronic stroke participants underwent three repetitive transcranial magnetic stimulation (rTMS) sessions: inhibitory 1 Hz rTMS to contralesional M1, facilitatory 5 Hz rTMS to cPMd, and sham rTMS. Motor performance on a reaching task (RT) was assessed pre- and post-stimulation. Baseline assessments included UE Fugl-Meyer (UEFM), corticospinal integrity (fractional anisotropy), and motor evoked potentials (MEPs). Classification and Regression Tree (CART) analysis identified UEFM 42 as the threshold distinguishing patients who improved with cM1 inhibition versus cPMd facilitation rTMS, with 91.6 % and 83.3 % accuracy, respectively. Participants with UEFM>42 showed greater RT gains with inhibitory rTMS than more severely impaired individuals (p = 0.06), whereas those with UEFM≤42 demonstrated greater RT gains with facilitatory cPMd rTMS than sham (p = 0.003). Less-severe participants had larger increases in ipsilesional MEPs following inhibitory rTMS (p = 0.007), whereas more-severe (UEFM≤42) MEP-absent participants had larger reductions in interhemispheric inhibition (IHI) following facilitatory cPMd rTMS (p = 0.028). Our findings support the bimodal theory and introduce the START (Stratification Algorithm for rTMS) framework, utilizing clinical impairment and white matter integrity to stratify response. While promising, the START algorithm requires further validation in larger samples to develop targeted and effective neuromodulation treatments. •UE-Fugl Meyer (UEFM) score of 42 stratifies patients for contralesional rTMS.•Less impaired patients (UEFM >42) improve with contralesional inhibition rTMS.•More impaired patients UEFM ≤42) improve with contralesional facilitation rTMS.